Insights into temperature modulation of the Eucalyptus globulus and Eucalyptus grandis antioxidant and lignification subproteomes - Santana Costa, Marilia Gabriela de [UNESP]; Mazzafera, Paulo; Balbuena, Tiago Santana [UNESP] (Elsevier B.V., 2017)
Eucalyptus grandis and Eucalyptus globulus are among the most widely cultivated trees, differing in lignin composition and plantation areas, as E. grandis is mostly cultivated in tropical regions while E. globulus is preferred in temperate areas. As temperature is a key modulator in plant metabolism, a large-scale proteome analysis was carried out to investigate changes in the antioxidant system and the lignificadon metabolism in plantlets grown at different temperatures. Our strategy allowed the identification of 3111 stem proteins. A total of 103 antioxidant proteins were detected in the stems of both species. Hierarchical clustering revealed that alterations in the antioxidant proteins are more prominent when Eucalyptus seedlings were exposed to high temperature and that the superoxide isoforms coded by the gene Eucgr.B03930 are the most abundant antioxidant enzymes induced by thermal stimulus. Regarding the lignin biosynthesis, our proteomics approach resulted in the identification of 13 of the 17 core proteins involved in this metabolism, corroborating with gene predictions and the proposed lignin toolbox. Quantitative analyses revealed significant differences in 8 protein isoforms, including the ferulate 5-hydroxylase isoform F5H1, a key enzyme in catalyzing the synthesis of sinapyl alcohol, and the cinnamyl alcohol dehydrogenase isoform CAD2, the last enzyme in monolignol biosynthesis. Data are available via ProteomeXchange with identifier PXD005743. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Lignocellulose biomass; Mass spectrometry; Plant-environment interaction; Tree physiology